EFFECTS OF SLIDING DISTANCE SPEED AND LOAD ON WEAR AND TEMPERATURE IN DIFFERENT MATRIX AND FIBER-REINFORCED COMPOSITE MATERIALS - Pıhtılı, Haşim (Hibetullah KILIÇ, 2021)
In this study, wear behaviours of fiber-reinforced and matrix composite materials are experimentally investigated under different speeds, loads and temperature. Composite materials were made of Kevlar-epoxy resin, glass fibre-epoxy resin and glass fibre -polyester resin materials. Tests were conducted for speeds of 0,390 and 0,557 m/s , at two different loads of 5N and 10N, respectively. Wear in the experiments was determined as lost in mass. In addition, the photographs of specimens were taken under the SEM and wear behaviours on these photographs were investigated. As a result of this study, it is shown that the applied load on the specimens has more effect on the wear than that of speed. The surface temperature plays an important role in the friction and wear of polymers and increases at higher sliding speeds and loads. The temperature of the specimens increased more with the increasing sliding speed and applied load, so the wear increases more with the temperature.
Keywords: Mechanical Engineering; Makine Mühendisliği